Perspectives of Corporate Governance in Croatian Banking Sector - Golja, Tea; KrstiniÄ‡ NiÅ¾iÄ‡, Marinela; PauliÅ¡iÄ‡, Morena (International Journal of Economics and Financial Issues, 2011)
Financial market of any country firstly has to be “secure”, but although financial market is regulated and monitored, we were witnesses of bad examples (Island). So, globally all aspects of corporate governance became interesting: ownership; nature of activities; liquidity ratios, etc. The goal of this paper is to give perspectives of corporate governance in Croatian banking sector. The results of the research conducted in October 2010 are presented. The situation regarding corporate governance issues in banks is highlighted. According to the research in Croatian banks in the future corporate governance should give more attention to responsiveness; equity; efficiency and effectiveness; and on accountability. Mentioned principles are not clearly defined and recognizable. These will assure differentiation on market and trust of all stakeholders. Keywords: Corporate governance; Banking sector; Republic of Croatia JEL Classifications: D22; K23; M14